Rare earth elements in oysters and mussels collected from the Chinese coast: Bioaccumulation and human health risks. (November 2022) - Zhao, Puhui; Bi, Ran; Sanganyado, Edmond; Zeng, Xiangfeng; Li, Weiwen; Lyu, Zhendong; Liu, Jinyan; Li, Ping; Du, Hong; Liu, Wenhua; Jia, Yongfeng
Abstract: Rare earth elements (REEs) are increasingly used in various industries worldwide, resulting in their release into aquatic ecosystems. We evaluated the distribution and bioaccumulation of 14 REEs in marine sediments and biotas along the Chinese coasts. The total concentration of REEs (ΣREEs) in sediments was 41.65–170.94 mg/kg. The concentrations of ΣREEs were 1.97–4.77 and 0.62–4.96 mg/kg dry mass (DM) for oysters and mussels. The concentration of total light REEs (ΣLREEs) was higher than the concentration of total heavy REEs (ΣHREEs) at all samples. The bioaccumulation factor (BAF) of ΣLREEs was higher than ΣHREEs and BAF of ΣREE was 0.34–1.49 and 0.25–1.10 for oysters and mussels. The positive correlation between sediments and biotas was higher in mussels than oysters, showing a good potential for being environmental indicators for REEs. The risk of REEs to humans via oysters and mussels consumption could be negligible based on the estimated daily intake. Graphical abstract: Unlabelled Image Highlights: Light REEs were easily enriched in filter feeder species than heavy REEs. Bivalves have higher capacity in accumulating REEs than other marine biotas. Mussels were more suitable being as indicator species for REEs than oysters. Risk of REEs exposure to humans via oysters and mussels consumption was negligible.